2010
DOI: 10.1093/hmg/ddq247
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calcium uptake capacity as a therapeutic target in the R6/2 mouse model of Huntington's disease

Abstract: Huntington's disease (HD) is an incurable autosomal-dominant neurodegenerative disorder initiated by an abnormally expanded polyglutamine domain in the huntingtin protein. It is proposed that abnormal mitochondrial Ca2+ capacity results in an increased susceptibility to mitochondrial permeability transition (MPT) induction that may contribute significantly to HD pathogenesis. The in vivo contribution of these hypothesized defects remains to be elucidated. In this proof-of-principle study, we examined whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 69 publications
1
31
1
Order By: Relevance
“…These results suggest that the protective effect of RSG and the higher susceptibility of STHdh Q111 cells to TG may not be related to mPTP. Similarly, a recent study using R6/2 mice crossed with CypD knockout mice demonstrated that the deletion of CypD in the R6/2 mice resulted in enhanced mitochondrial Ca 2+ buffering but did not show any improvement in the pathogenic symptoms or a delay in disease progression [45]. Further, RSG has been reported to protect cells against stresses by upregulation of PPARγ and Bcl-2, an anti-apoptotic protein that has been shown to be implicated with HD [14], [46].…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that the protective effect of RSG and the higher susceptibility of STHdh Q111 cells to TG may not be related to mPTP. Similarly, a recent study using R6/2 mice crossed with CypD knockout mice demonstrated that the deletion of CypD in the R6/2 mice resulted in enhanced mitochondrial Ca 2+ buffering but did not show any improvement in the pathogenic symptoms or a delay in disease progression [45]. Further, RSG has been reported to protect cells against stresses by upregulation of PPARγ and Bcl-2, an anti-apoptotic protein that has been shown to be implicated with HD [14], [46].…”
Section: Discussionmentioning
confidence: 95%
“…This idea was reinforced by the fact that CypD is upregulated in Huntington's patients and that this upregulation increased as Huntington's disease progressed (Shirendeb et al., 2011). However, other reports did not find such significant contribution of mPTP to mitochondrial injury in Huntington's disease, demonstrating that genetic inactivation of CypD does not modify the onset and the progression of the disease in mice (Brustovetsky et al., 2005; Pellman, Hamilton, Brustovetsky, & Brustovetsky, 2015; Perry et al., 2010). …”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%
“…HD is caused by an aberrant expansion of the CAG repeat domain within exon one of the huntingtin (htt) gene (Group 1993). At the cellular level mutant htt (mthtt) interferes with various functions including transcriptional regulation (Luthi-Carter, Hanson et al 2002; Hodges, Strand et al 2006; Bithell, Johnson et al 2009), the maintenance of calcium homeostasis (Perry, Tallaksen-Greene et al 2010; Giacomello, Hudec et al 2011), and synaptic physiology (Klapstein, Fisher et al 2001; Milnerwood and Raymond 2007; Cummings, Andre et al 2009). …”
Section: Introductionmentioning
confidence: 99%